Making sure of survival: Reflections on the report - Karl Wolfgang Menck (Intereconomics, 1980)
Early in 1980—well before the Special Session of the UN General Assembly in New York—the Independent Commission for International Development Issues chaired by Willy Brandt presented its Report: “North-South: A Programme for Survival”. The findings of the Commission which is better known as “North-South Commission” or “Brandt Commission” have met with agreement and approval but also with criticism. Which recommendations has the Commission made? Which points of the Report are being criticised?
Keywords: 330; North-South Commission